Hierarchical Wide-Area Control of Power Systems Including Wind Farms and FACTS for Short-Term Frequency Regulation - Leon, Enrique Andres (2012)
In this work a hierarchical scheme is proposed for the coordinated control of conventional synchronous generators, wind farm converters and flexible ac transmission systems. It comprises two levels, namely a fully decentralized set of controllers associated with the involved devices and a centralized coordinating controller based on synchronized wide-area signals provided by phasor measurement units. The proposed hierarchy of controllers is mainly focused on two objectives: transient frequency support and inter-area oscillations damping. Recent works have recently proved that the fast-acting power converters of variable-speed generators can greatly improve the short-term frequency regulation capability in scenarios with a large penetration of wind energy. A case study is included showing that the dynamic performance and stability of power systems can indeed be enhanced when local windmill converters are properly coordinated via a wide-area centralized controller.